Diglossia in Ghanaian Society and Its Negative Influence on Students' Proficiency in English: A Case Study on Three Town Senior High School Students - Abdullah Sulaiman, Ibrahim (International Journal of Language and Literary Studies, 2024)
Ghanaian Pidgin English (GPE) has gained widespread usage in various official and educational institutions across Ghana, transcending its traditional boundaries. This study aims to investigate the phenomenon of diglossia in Ghanaian society. Particularly, it seeks to examine GPE, exploring its emergence, development, varieties, and negative effects on Three Twon Senior High School (THREESEC) students’ academic performance in standard English. The study employs a descriptive-analytical research design to describe and analyze GPE within Ghanaian society, particularly within the Ketu South district. Additionally, it utilizes a quantitative approach to analyze results obtained from a series of questionnaires, aiming to understand the impact of GPE on THREESEC students' proficiency in English. The study reveals that most of the targeted students acknowledge that GPE has negatively affected their speaking skills. At the same time, a minority admit that it has adversely impacted their writing skills. Therefore, the study recommends that relevant stakeholders in Ghanaian society, particularly within the Ketu South community and school officials, implement necessary and stringent measures to limit the spread of this variety of English and discourage its use in educational institutions before it becomes too pervasive.